Debating the Jinn: Making and unmaking of the invisible beings in the discursive tradition of Malabar. (1st December 2019) - Chenganakkattil, Muhamed Riyaz
AbstractThis article is an addition to the culture of 'debate as performance' in the Indian subcontinent as a research on the theological arguments through texts and performances on the existence of invisible creatures. It locates the space of the debates in Malabar, which has a long history of argumentative tradition. This article suggests that (in)visibility is the central point of contestation when one analyses the debating culture on Jinns. Textual representation of arguments and performance on the stage are two spaces where we can analytically explore the cases. The Jinn debate has undergone transitions in its development towards a core ideological point in Malabar. How do proponents and opponents corroborate their arguments based on texts or the logical understanding? When has this practice begun? Who were the leading Jinn debaters in Malabar? Malabar, as a discursive space for debates, has contributed to the making and unmaking of Jinns in the region. It is obvious that these debates were performative events, as a performance of the pure religion, and as a performative moment for distinctions for each ideology from the other.